THE STRUCTURE OF PATRIOTISM AS A UNIVERSAL VALUE IN THE SYSTEM OF VALUE ORIENTATIONS OF RUSSIAN STUDENTS AND ITS PRACTICAL PROJECTIONS - Chekmenev, Dmitry; Efimova, Ekaterina; Davydova, Elena (Journal of Sociology: Bulletin of Yerevan University, 2024)
The article delves into the structural aspects of patriotism as a universal value within the value system of Russian student youth. It aims to pinpoint and analyze practical manifestations of patriotism among this demographic. The relevance of this study is underscored by several factors: the presence of various external threats that necessitate a strong societal cohesion, with patriotism serving as a key factor in achieving this; and the ongoing efforts in contemporary Russia to reinforce traditional values, including patriotism, making it crucial to understand how these values are embraced by student youth. The authors of the article aim to analyze the ways in which patriotic values are expressed among Russian student youth. They utilize empirical data gathered from completed questionnaires by first-year students who participated in the competition "Facts of Russian Statehood." By examining these materials, the researchers seek to identify and generalize the specific features of how patriotism is manifested among this demographic. The authors highlight the features of the patriotic manifestation among students in the content aspect (patriotism is a broad category), associative (patriotism is a multi-level concept), and activity (patriotism has a clear practical content).